FOXO3a (Forkhead Transcription Factor O Subfamily Member 3a) Links Vascular Smooth Muscle Cell Apoptosis, Matrix Breakdown, Atherosclerosis, and Vascular Remodeling Through a Novel Pathway Involving MMP13 (Matrix Metalloproteinase 13). Issue 3 (March 2018) - Yu, Haixiang; Fellows, Adam; Foote, Kirsty; Yang, Zhaoqing; Figg, Nichola; Littlewood, Trevor; Bennett, Martin
Abstract : Objective—: Vascular smooth muscle cell (VSMC) apoptosis accelerates atherosclerosis and promotes breakdown of the extracellular matrix, but the mechanistic links between these 2 processes are unknown. The forkhead protein FOXO3a (forkhead transcription factor O subfamily member 3a) is activated in human atherosclerosis and induces a range of proapoptotic and other transcriptional targets. We, therefore, determined the mechanisms and consequences of FOXO3a activation in atherosclerosis and arterial remodeling after injury. Approach and Results—: Expression of a conditional FOXO3a allele (FOXO3aA3ER) potently induced VSMC apoptosis, expression and activation of MMP13 (matrix metalloproteinase 13), and downregulation of endogenous TIMPs (tissue inhibitors of MMPs). mmp13 and mmp2 were direct FOXO3a transcriptional targets in VSMCs. Activation of endogenous FOXO3a also induced MMP13, extracellular matrix degradation, and apoptosis, and MMP13-specific inhibitors and fibronectin reduced FOXO3a-mediated apoptosis. FOXO3a activation in mice with VSMC-restricted FOXO3aA3ER induced MMP13 expression and activity and medial VSMC apoptosis. FOXO3a activation in FOXO3aA3ER/ApoE −/− (apolipoprotein E deficient) mice increased atherosclerosis, increased necrotic core and reduced fibrous cap areas, and induced features of medial degeneration. After carotid artery ligation, FOXO3a activation increased VSMC apoptosis, VSMC proliferation, and neointima formation, all of which were reduced by MMP13 inhibition. Conclusions—: FOXO3a activation induces VSMC apoptosis and extracellular matrix breakdown, in part, because of transcriptional activation of MMP13. FOXO3a activation promotes atherosclerosis and medial degeneration and increases neointima after injury that is partly dependent on MMP13. FOXO3a-induced MMP activation represents a direct mechanistic link between VSMC apoptosis and matrix breakdown in vascular disease. Abstract : Supplemental Digital Content is available in the text.